The ability of anti-carbonic anhydrase II antibody to distinguish autoimmune cholangitis from primary biliary cirrhosis in Japanese patients - Akisawa, Naoaki; Nishimori, Isao; Miyaji, Eiki; Iwasaki, Shinji; Maeda, Takashi; Shimizu, Hidetake; Sato, Nobuhiro; Onishi, Saburo (Journal of gastroenterology, 1999)
Serum antibody against carbonic anhydrase (CA) II has been described as a serological marker for distinguishing autoimmune cholangitis (AIC) from primary biliary cirrhosis (PBC). To validate this finding in a Japanese population, we evaluated sera from patients with PBC and AIC for antibody to human CA II. An enzyme-linked immunosorbent assay was employed to quantify serum antibody against CA II in patients with PBC (n = 40), AIC (n = 23), autoimmune hepatitis (n = 10), and extrahepatic obstructive jaundice (n = 10). Compared with the finding of a 4% prevalence of anti-CAII antibody in healthy subjects (n = 24), a significantly higher prevalence of anti-CA II antibody was detected in patients with PBC (35%) and AIC (30%) (P < 0.05), but not in patients with autoimmune hepatitis and patients with obstructive jaundice. No significant difference was observed between PBC and AIC patients. These results showed that AIC and PBC would be indistinguishable by anti-CA II antibody testing in Japanese patients. However, the finding of serum anti-CA II antibody in patients with PBC and AIC supports the disease concept of autoimmune exocrinopathy.